(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to improve the learning outcomes of football dribbling skills through the coercion method in seventh-grade students of Al Falah Islamic Middle School. The hypothesis put forward is that the resonance method can effectively improve students’ mastery of dribbling techniques. This study is a Classroom Action Research (CAR) conducted in two cycles that include the stages of planning, action, observation, and reflection. The research subjects numbered 11 students. Data collection techniques included observation, skills tests, and documentation, with assessments based on nine aspects of motor skills. The results of the study showed a significant increase from cycle I to cycle II, where in cycle I only 4 students (36%) completed the learning, while in cycle II this increased to 10 students (90%). An increase in the average score and learning outcome categories was also seen, with the dominance of the "Very Good" and "Good" categories in cycle II. These results indicate that the enhancement method is effective in improving students’ mastery of dribbling techniques individually and as a class. The implications of these findings indicate the importance of using visual approaches and direct practice in physical education learning.